Retraction of published article due to the author's proposal, Vol. 2021, Iss. 3, pp. 375-387 - Serhiy O. Semerikov (Academy of Cognitive and Natural Sciences, 2022)
The editorial board of Educational Technology Quarterly, announces the formal Retraction of the following article: Pursky, O., Selivanova, A., Buchatska, I., Dubovyk, T., Tomashevska, T. and Danylchuk, H., 2021. Features of learning motivation in the conditions of coronavirus pandemic (COVID-19). Educational Technology Quarterly, 2021(3), pp. 375-387. Available from: https://doi.org/10.55056/etq.31